Stor andel multipel psykisk ohälsa i familjer aktuella för behandlingsinsatser i Barn- och Vuxenpsykiatri - erfarenheter av endagsinventering i klinisk vardag - Linderborg, Camilla; Rydén, Göran; Berntsson, Anders; Östman, Margareta (Socialmedicinsk tidskrift, 2022)
Abstract An operational development project carried out in Child and Adult Psychiatry outpatient care in Stockholm shows that half of the patients in child psychiatry and one third of the patients in adult psychiatry live in families with multiple mental illness. Repeated one-day inventories of the treatment's knowledge of mental illness in the families form the basis of the results. Both operations have employees who see the complex situation of families, without offering elaborate forms of resource use between the structures. The existing individual centering focus and the lack of integration between organizations need to be called into question in order to develop models for vulnerable families. One approach is to introduce a family model, with the aim of influencing support to families where both children and parents have mental illness.